2019
DOI: 10.5603/njo.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

SOX10 as an immunohistochemical marker in cancer diagnostics

Abstract: SOX10 is a transcription factor that plays an important role in the formation, speci cation and di erentiation of neural crest cells. Recent studies indicate that this protein is expressed in tumors of the nervous system, salivary glands, breast, soft tissues and melanoma cells. Due to its higher sensitivity and speci city in comparison to other available markers, SOX10 protein is mainly used in the diagnosis of malignant peripheral nerve sheet tumor and primary and metastatic melanoma including desmoplastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Zhou et al demonstrated that inhibition of histone 3 methyltransferase EZH2, specifically at the position of lysine 3 (H3K27me3), through processes such as methylation, 7e-methylation, and trimethylation, initiated the development of myeloid-derived suppressor cells (MDSC) [89]. As a result, favorable conditions for anti-inflammatory action appeared in IBD therapy [90]. Another analysis presented H3K27me3 as a protein that could potentially control extracellular vesicles to regulate Th17 in patients with UC [91].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Zhou et al demonstrated that inhibition of histone 3 methyltransferase EZH2, specifically at the position of lysine 3 (H3K27me3), through processes such as methylation, 7e-methylation, and trimethylation, initiated the development of myeloid-derived suppressor cells (MDSC) [89]. As a result, favorable conditions for anti-inflammatory action appeared in IBD therapy [90]. Another analysis presented H3K27me3 as a protein that could potentially control extracellular vesicles to regulate Th17 in patients with UC [91].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…39,[50][51][52] However, immunohistochemical staining of these molecules both in the nucleus and in the cytoplasm has been also described. 53,54 The predominantly nuclear localization of MITF and SOX-10 overcomes the problem of the dendritic process and melanocytic hyperplasia in sun-damaged skin and AK suggested by Melan-A staining. Moreover, in the case of using 3,3 0 -diaminobenzidine of brown color as a chromogen in immunohistochemistry, the nuclear staining pattern allows for its more precise differentiation from the melanin background.…”
Section: Mitf and Sox-10mentioning
confidence: 99%
“…Both MITF and SOX‐10 proteins function in the same signaling pathway in melanocytes and, being transcription factors, are mainly localized in the nucleus 39,50–52 . However, immunohistochemical staining of these molecules both in the nucleus and in the cytoplasm has been also described 53,54 . The predominantly nuclear localization of MITF and SOX‐10 overcomes the problem of the dendritic process and melanocytic hyperplasia in sun‐damaged skin and AK suggested by Melan‐A staining.…”
Section: Immunohistochemical Detectability Of Melanocytes In Intraepi...mentioning
confidence: 99%
“…PD-L1 is the ligand of PD-1 which is upregulated by exhausted T cells and reduces T-cell effector functions upon binding with its ligand ( Parry et al, 2005 ). SOX10 is a transcription factor that plays an important role in characterising neural crest cell and is a reliable, sensitive, and specific nuclear marker used for the detection of metastatic melanoma ( Pytlak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%